Characterization of macrophages, giant cells and granulomas during muscle regeneration after irradiation. (January 2021) - Nikovics, Krisztina; Favier, Anne-Laure; Barbier, Laure; Drouet, Michel; Riccobono, Diane
Highlights: ASC cells play an important role in improving tissue regeneration. Majority of the Macrophages show strong IL-6 expression. The CD4 + cells produce IL-1β cytokines. IL-10 expressing muscle means improved regeneration. Muscle producing IL-4 may explain the presence of giant cells in the sample. Abstract: Macrophages play a fundamental role in the different stages of muscle regeneration although the precise mechanisms involved are not entirely understood. Here we investigated the types of macrophages and cytokines that appeared in muscles after local gamma irradiation of mini-pigs that underwent no subsequent treatment or received three successive adipose tissue-derived stem cell (ASC) injections. Although some variability was observed among the three animals included in each study group, a general picture emerged. No macrophages appeared in control muscles from regions that had not been irradiated nor in muscles from irradiated regions derived from two animals. A third irradiated, but untreated animal, with characteristic muscle fibrosis and necrosis due to irradiation, showed invasion of M2 macrophages within small muscle lesions. In contrast, among the three ASC-treated and irradiated animals, one of them had completely recovered normal muscle architecture at the time of sampling with no invading macrophages, muscle from a second one contained mostly M1 macrophages and some M2-like macrophages whereas muscle from a third one displayed granulomas and giant cells. ASC treatment was associated with the presence of similar levels of pro-inflammatory cytokines within the two animals in the process of muscle regeneration whereas the levels of IL-4 and IL-10 expression were distinct from one animal to another. Microspectrofluorimetry and in situ hybridization revealed strong expression of TGF-β1 and TNFα in regenerating muscle. Overall, the data confirm the critical role of macrophages in muscle regeneration and suggest the involvement of a complex network of cytokine expression for successful recovery.